2017
DOI: 10.1111/flan.12294
|View full text |Cite
|
Sign up to set email alerts
|

The Undergraduate Spanish Major Curriculum: Faculty, Alumni, and Student Perceptions

Abstract: This article presents the quantitative and qualitative results of a nationwide survey of the perceptions of faculty, alumni, and students regarding the contribution to the undergraduate Spanish major curriculum of various types of courses and experiences. Quantitative results indicated that all participants valued the importance of study abroad as well as advanced composition and grammar courses. Significant differences were found in the relative importance of other components of the undergraduate curriculum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In other words, they can be more easily adapted to learners' unique situations, which means that learners are more likely to find them relevant, adequately difficult, focus-worthy, and flowgenerating. The relationship between communicationfocused authentic activities and flow also makes sense considering that most learners study languages to communicate with those who speak that language (Hertel & Dings, 2017;Knouse et al, 2021;Magnan et al, 2014). As a result, learners are likely to believe that authentic activities will help them become L2 selves who are more connected to envisioned imagined communities and thus focus on them.…”
Section: The Current State Of L2 Flow Researchmentioning
confidence: 99%
“…In other words, they can be more easily adapted to learners' unique situations, which means that learners are more likely to find them relevant, adequately difficult, focus-worthy, and flowgenerating. The relationship between communicationfocused authentic activities and flow also makes sense considering that most learners study languages to communicate with those who speak that language (Hertel & Dings, 2017;Knouse et al, 2021;Magnan et al, 2014). As a result, learners are likely to believe that authentic activities will help them become L2 selves who are more connected to envisioned imagined communities and thus focus on them.…”
Section: The Current State Of L2 Flow Researchmentioning
confidence: 99%
“…Not only are there divisions between the language and literature sides of the undergraduate curriculum, but divisions also exist among departmental stakeholders and their language teaching and learning goals. For instance, two recent studies revealed that students valued more instrumental goals of FL study such as oral communication, cultural products, and connections to other disciplines, whereas instructors valued more intellectual goals such as literature and culture learning, critical thinking, and cultural perspectives (Hertel & Dings, ; Mills & Moulton, ). These persistent divisions have impacted FL enrollments and prevented colleagues from acknowledging what they share in common: the enterprise of educating learners about and through the languages, texts, and perspectives of different cultures.…”
Section: Literacies and Textual Thinkingmentioning
confidence: 99%
“…Their reflections on and descriptions of the instruction they received provide insight into which aspects of writing were emphasized during instruction and what form writing instruction took in advanced Spanish studies courses. In addition, the study explored both students' and faculty members' perceptions of students' writing abilities and thus extends a body of research that brings together multiple stakeholder perspectives (e.g., Hertel & Dings, 2017;Magnan et al, 2014;Mills & Moulton, 2017;Rifkin, 2012). These issues were explored across the major curriculum with the goal of understanding current practices, strengths, and opportunities for growth from the perspective of both faculty and student stakeholders.…”
Section: Introductionmentioning
confidence: 99%